1997
DOI: 10.1074/jbc.272.29.18216
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Cardiac Muscle Troponin C Unexpectedly Reveals a Closed Regulatory Domain

Abstract: The regulation of cardiac muscle contraction must differ from that of skeletal muscles to effect different physiological and contractile properties. Cardiac troponin C (TnC), the key regulator of cardiac muscle contraction, possesses different functional and Ca 2؉ -binding properties compared with skeletal TnC and features a Ca 2؉ -binding site I, which is naturally inactive. The structure of cardiac TnC in the Ca 2؉ -saturated state has been determined by nuclear magnetic resonance spectroscopy. The regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
249
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(270 citation statements)
references
References 35 publications
(29 reference statements)
17
249
1
2
Order By: Relevance
“…Ca 2þ bound, closed EF-hand has only been reported for two other EF-hand calcium sensors [calpain 40 and cardiac troponin C (cTnC) 41 ] and in the pseudo-EF-hand of S100 proteins (calcyclin 42 and S100B 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2þ bound, closed EF-hand has only been reported for two other EF-hand calcium sensors [calpain 40 and cardiac troponin C (cTnC) 41 ] and in the pseudo-EF-hand of S100 proteins (calcyclin 42 and S100B 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…cNTnC mutants have been used in previous studies to examine the structure and Ca 2ϩ activation of the NH 2 -terminal domain (20,34,35). Spyracopoulos et al (35) have demonstrated that the Ca 2ϩ -saturated NMR solution structure of McNTnC is similar to that of the Ca 2ϩ -saturated NH 2 domain of the full-length mutant (C35S/C84S) chicken cTnC (33). In the present study, ScNTnC and McNTnC had a higher Ca 2ϩ affin- ity than the respective full-length isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…SANS studies of the ternary cTn further revealed the effect of phosphorylation of the two protein kinase A dependent phosphorylation sites in the cardiac-specific N-terminal extension in cTnI ($ 27-33 residues); this phosphorylation in known to result in a reduction in myofilament Ca 21 sensitivity and an increase in relaxation and cross-bridging cycle kinetics. [25][26][27] All of the high-resolution structures of sTnC and cTnC show the characteristic dumbbell shape with two globular domains separated by an extended, solvent-exposed helix of 7-8 turns [28][29][30][31][32] 41 and Heidorn and Trewhella 42 presented the first SAXS studies of rabbit sTnC that showed that the two globular domains of sTnC are on average closer together in solution than they are in the crystal structure. This interpretation was evident in the P(r) profile, which showed a peak with a shoulder in the distribution rather than the two resolved peaks indicative of two separate domains and suggested that, like calmodulin, the helix connecting the two globular EF-hand domains was flexible in solution.…”
Section: Skeletal and Cardiac Isoforms Of Troponinmentioning
confidence: 99%